RANCANGAN PEMBANGKIT LISTRIK TENAGA PIKOHIDRO MEMANFAATKAN SIRKULASI AIR KOLAM - Leily Wustha Johar; Fadli Eka Yandra; H. Myson (Jurnal Cakrawala Ilmiah, 2023)
Picohydro Power Plant (PLTPH) is designed for water with a small flow, the design of this PLTPH does not require complicated construction with output reaching several kilowatts. This design uses materials that can be found easily and are widely available. The turbine is made using a sand shovel, and the reservoir used is a used drum, using a DC generator, inverter circuit, battery and other supporting tools. This design produces a nominal power of 450 watts which is used for lighting around the pool